Analysis Of Catching Technique Skills In Ukm Cricket Athletes Of Jambi University - Putri, Dini Amelia; Ali, Muhammad; Putra, Anggrawan Januar (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to analyze the catching technique skills of athletes from the Jambi University Cricket Student Activity Unit (UKM). Catching technique is one of the fundamental aspects in cricket that greatly determines the success of the team, especially in preventing the opponent from scoring points. This study uses a quantitative descriptive method with a survey approach. The sample in this study were all members of the Jambi University Cricket UKM totaling 20 people (10 male and 10 female), who were selected using the total sampling technique. The instrument used was an observation sheet for catching technique skills, which included four stages of catching technique: basic, bouncing bottom ball, rolling bottom ball, and top ball. The results showed that 25% of athletes were in the